Perfil clínico da gestação tardia: enfoque para promoção da saúde - Camargo, Carla Regina Moreira (2018)
Purpose: Late pregnancy has had a considerable increase in recent years in Brazil. Postponement of pregnancy occurs due to adverse reasons and therefore has a higher risk of developing maternal, fetal and neonatal complications. The prenatal period becomes a propitious moment to promote the health of these women, as well as gathering knowledge and knowledge of different professionals for a quality care, favors the bond and promotes a more humanized care. Objective: To describe the clinical profile of the pregnant woman aged 35 years or over in a referral hospital in the triple border and to identify strategies in health education to promote the health of late pregnant women. Method: A retrospective, quantitative study, carried out in the first semester of 2017, composed of women aged 35 years or over who underwent the birth process in the period from 2012 to 2016 in a hospital institution of reference for high risk gestation in Foz do Iguaçu-PR. Data were tabulated in Microsoft Excel ® spreadsheets. Data were analyzed using a Chi square test, using a significance level of 5% and p value of <0.05. Results: During the period from 2012 to 2016, 2,605 deliveries of women aged 35 years or more occurred, which has shown an increase in deliveries in late pregnant women; in terms of nationality, the Brazilian women were the majority, the hospital occupation was higher by the system. Most of the gestational complications were arterial hypertension, diabetes mellitus, and preeclampsia. The surgical delivery had a higher incidence for prematurity, low birth weight, and as neonatal outcome, the neonatal therapy unit. Conclusion: Through the characterization of the clinical profile of late pregnant women, it did not show a different profile of the reality of other municipalities and that health education actions through meetings, booklet, and individual reception, can be carried out as a strategy for the health promotion.